Digital management of multiple advertising displays - Baptista, Arménio Ferreira (2019)
The technological boom that we have been experiencing in the last decade has impacted the retail sector in several ways. Captivating customers through smart advertising, engaging them in the retail process and enhancing their experience has been a long-time desideratum in this industry. Recent technology makes it possible to follow unprecedented approaches for achieving these goals. In this thesis, we present a solution based on a series of autonomous stations (either static, such as monitors, or mobile, such as autonomous robots) that can be used in any type of multimedia advertising across one or multiple entities. The main core of the presented solution is a Web Server that can store the uploaded contents, which exposes a web dashboard for their management. Registered users can manage and distribute the contents through the connected terminals (or agents), being the only requirement a network connection between the server and the agents. We present results of this system within several research events that took place within the local academic environment. The system was used with the aim of automatizing the dissemination and advertising of local research works. Ultimately, we expect to extend its use to the retail sector in an attempt to impact modern advertising.